Reclaiming the Jesus of history : Christology today - Eckardt, A. Roy (Arthur Roy), 1918-1998 (Minneapolis, Fortress Press, 1992)
"A sympathetic reading of Jesus the champion of Israel that seeks to avoid Chrisitian triumphalism and elitism which have frustrated past efforts for a mutual understanding between Judaism and Christianity." - from book jacket
Preface -- Part 1: Preliminaries: 1. Journey into the apostolic past: Three Christological assumptions - Four negations - History-truth-reason - The way of historicalness -- 2. Synoptic titles: Jesus' titles and Jesus' identity - Prophet - Lord - Messiah - Son of God -- Part 2: Five Historical Images: 3. The Judaism of Jesus, countercultural spiritualizer: A new vision of Jesus - Jesus and the Spirit - Jesus and culture - Assessment of Marcus Borg - Excursus: can there be a holy secularity? -- 4. The Judaism of Jesus, rejected advocate of Israel's restoration: Jewish restoration eschatology - The kingdom of God - Jesus: conflict and death -- 5. The Judaism of Jesus, champion of Israel: Getting ready for the kingdom - The kingdom and the king - Beyond the failure of Jesus: The Torah of God - The opening of the covenant - Excursus: Crucis personae -- 6. The Judaism of Jesus, liberator of the wretched: The quality of liberation - Jesus and human liberation - Segundo, Jesus, and the kingdom - Fiorenza, Christian origins, and female liberation - A few working remarks -- 7. The Judaism of Jesus, Redeemer of women: Sanguine viewpoints - Negativist views - Transformationist positions -- Part 3: From Jesus to Christ: Discontinuity and continuity: The Christs of the apostolic writings: Methodological and hermeneutical questions - Discontinuities between the Jesus of history and the Christ of faith - Continuities between the Jesus of history and the Christ of faith - A Neokenotic possibility -- 9. The Convental Christ: Van Buren's task - Van Buren and other Christologists - Two areas of debate - Twelve questions -- 10. Jesus Christ and "the Great Ways of Humankind": Ten pillars - The typology of Paul F. Knitter - Knitter's own Christology - Again Neokenosis -- 11. Restoring the Resurrection: "Why do you search among the dead?: Thesis: pedestrian acknowledgment (1942074) - Antithesis: critical questioning of the thesis upon moral grounds (1975-86)- Synthesis: antitriumphalist affirmation (1987ff.) -- 12. For the sake of Rachel and the sake of Sarah: Toward a postmodern Christology: Jesus-Israel-Liberation-Salvation - A dialectic of two worlds - The hiding and the giving -- Epilogue: John Macquarrie's Jesus Christ in Modern Thought
Includes bibliographical references (pages 271-275) and indexes
Keywords: Jesus Christ -- Person and offices; Jesus Christ -- Jewishness